How Does Self-Control Moderate Shopping Enjoyment and Impulse Buying Among Generation Z Online Gamers? - Sherly Artadita; Sita Deliyana Firmialy (Bina Nusantara University, 2024)
In today’s technological age, access to the Internet is required in various fields, ranging from the essentials (clothing, food, and shelter) to recreation. As a result, people are willing to part with their money for the thrill of playing video games, which frequently leads to impulsive buying. Given this trend, the research examined why male and female gamers in Indonesia made impulsive purchases. The research employed quantitative sampling with a purposive sample type, specifically probability sampling. It looked at 220 Indonesian online Generation Z gamers who bought virtual goods in-game using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) model. From the results, three distinct phenomena are found. Firstly, evidence exists for the significant impact of shopping enjoyment on impulsive buying. Secondly, self-control has an insignificant role in preventing impulse buying. Lastly, the research offers insight into the insignificant role of self-control in moderating the relationship between shopping enjoyment and impulse buying. Among the three dimensions of self-control, cognitive control is the only dimension that has a significant effect on reducing the tendency of impulse buying among Generation Z online gamers. Additional research should assess the insignificant relationship between self-control and impulse buying, which may corroborate or contradict the research findings. Further investigation of potential intermediate variables (e.g., customer loyalty and brand relation) that connect self-control and impulse buying is also needed.